Agricultural SystemS and the Conservation of Biodiversity and Ecosystems in the Tropics - Goulart, F.F.; Jacobson, T.K.B.; Zimbres, B.Q.C.; Machado, R.B.; Aguiar, L.M.S.; Fernandes, G.W. (IntechOpen, 2012)
None